Malfeasance in the Charitable Sector: Determinants of "Soft" Corruption at Nonprofit Organizations. (2nd January 2019) - LeClair, Mark Steven
Abstract : The causes and effects of organizational corruption have been widely examined in the literature, including malfeasance that is specific to nonprofits organizations. This article draws a distinction between outright (illegal) and "soft" corruption—the latter referring to the continued and deliberate misuse of donated funds to benefit officers of the nonprofit, with little (in some instances less than 5%) going to the nonprofit's supposed cause. Soft corruption enables organizations to function essentially as counterfeit charities without risking legal peril. An empirical model encompassing approximately 450 randomly drawn nonprofits tests the determinants of this form of misbehavior. Ultimately it is shown that either the existence of an independent voting board or the conduct of an independent audit are the most important means of preventing soft corruption; far more important than state- or federally-mandated reporting requirements.